Pulperos, pardos and indepeendence in Venezuela. 1812-1814 - Tejada Soria, Jaika (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This essay aims to analyze how the whites, indigenous, duns and mulattos took part in the processes of independence of Caracas, in this respect, allusion is done to a conlict of races. A particular case is to try to consolidate that blacks and duns militias should be apart from the whites, this also is demonstrated in the payments, since the whites pay more than the blacks and the dun ones. In fact, the difference was kept between dun and white. These were the base of the irst pronouncement against the elite on the part of the dun ones, which it can turn as conlict of class.